Bullying and the Unique Experiences of Twice Exceptional Learners: Student Perspective Narratives. Issue 1 (January 2019) - Ronksley-Pavia, Michelle; Grootenboer, Peter; Pendergast, Donna
Bullying is known to be prevalent across social settings for children, particularly, for those who have disability and intermittently gifted students. What remains relatively underresearched is the phenomenon of bullying in the lives of twice-exceptional children. This article presents findings about the bullying experiences of eight twice-exceptional children aged 9 to 16 years from a study that explored the lived experiences of these children. Their narratives describe the pervasiveness of bullying. The six themes which emerged from the data about bullying experiences were (a) bullying by peers, (b) bullying by teachers, (c) teachers' and adults' responses to bullying, (d) social isolation and bullying, (e) the emotional effects of being bullied, and (f) protective factors. The contribution to the field of twice-exceptionality along with the children's experiences and consequences of being bullied are discussed. This article concludes with recommendations for practice and further research.